Pressão intraocular de cadelas das raças Shih-Tzu, Maltês e Lulu da Pomerânia por tonometria de aplanação - Ávila, Diego Fernando de (2012)
It was used 36 adult healthy dogs with no history of eye diseases, Shih-tzu, Maltese and Spitz breed (n = 12). The animals were subjected to tonometry applanation with Tonopen Vet over a 12 hours period to obtain the average values of the intraocular pressure IOP and verify the existence of circadian rhythm. It was Instilled a drop of anesthetic eye drops in each eye ten seconds before the IOP measurement and the bitches were physically contained in the sitting position, by the same examiner. The Shih-Tzu breed presented an intraocular pressure average of 16.19 mmHg in the right eye and 15.67 mmHg in the left eye, the Spitz breed presented 16.25 mmHg in the right eye and16.33 mmHg in the left eye, and finally the Maltese breed presented 13.0 mmHg in the right eye and 12.64 mmHg in the left eye. No one of the breed dogs was observed circadian variation of intraocular pressure in the 12 hours period.